Development of a Game-Based Learning: Airfield Lighting System Simulator Using Virtual Reality and Augmented Reality - Direstu Amalia; Viktor Suryan; Virma Septiani; Yeti Komalasari; Rio Rizko; Adha Febriansyah; Siti Salbiah Ristumanda; Muhammad Kristiawan; Oke Hendra (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aimed to develop an innovative learning tool, AIRLIT, as an alternative practical system to enhance the learning of Airfield Lighting System (ALS) among Diploma IV Airport Engineering Technology (DIV-TRBU) cadets. The motivation behind this research stemmed from the necessity to address the challenges faced in ALS practical learning due to limited access to airport facilities. The research methodology is Waterfall Model, encompassing phases: analysis, design, implementation, system testing, and maintenance. User needs were thoroughly analyzed, particularly those of DIV-TRBU cadets, through observations and interviews with subject matter experts. The resulting AIRLIT application offers immersive simulations of ALS operations, including AR recognition of lighting tools/materials and VR visualization of airport layouts. This research succeeded in developing the AIRLIT application, and system testing revealed positive outcomes, with the significant value for pair 1 is 0.000 < 0.05, so there is a difference in the average learning outcomes of cadets for the experimental class pre-test and the experimental class post-test. The significant value of pair 2 is 0.000 < 0.05, so there is a difference in the average learning outcomes of cadets for the control class pre-test and the control class post-test. The Independent sample test shows a difference in cadet learning outcomes between the learning model using AIRLIT and the conventional model, and this result indicates the effectiveness of AIRLIT in improving cadets' learning experiences and outcomes. Overall, this research underscores the significance of incorporating innovative technologies into educational practices, paving the way for enhanced learning experiences and outcomes in airport engineering training programs. The theoretical implication of this study lies in its contribution to integrating AR technology into educational settings, enhancing engagement and experiential learning. Practically, AIRLIT provides a valuable tool for ALS learning, addressing the limitations of traditional practical training methods.